Applying the self-determination theory in computer games for health communication. - Leow, Shallyn Xue Ling. (2012)
Serious games have been proven effective in achieving educational and health communication goals in past research for decades. However, the role of game enjoyment has not been considered as a main factor although it is one of the most important features in video games, and has been found to influence health-related outcomes in previous health communication game studies. Recent research showed that media enjoyment satisfies intrinsic needs, highlighting its importance in motivating individuals to perform specific tasks.